Intracranial Hemorrhage following Spinal Surgery: A Systematic Review of a Rare Complication - Al-Saadi, Tariq; Al-Kindi, Yahya; Allawati, Moosa; Al-Saadi, Hatem (The Surgery Journal, 2022)
Introduction Intracranial hemorrhage (ICH) is a potentially severe complication of spinal surgeries. The occurrence of such complications causes deterioration of the patient's clinical status and delayed discharge from the hospital. Although no specific etiological factors were identified for this complication, but multiple risk factors might play role in its development, they include the use of anticoagulants, presence of uncontrolled hypertension, and perioperative patient positioning.Aim A systematic review of the literature to investigate the prevalence of different types of intracranial hemorrhages in patients who underwent spinal surgeries.Methods A literature review was conducted using multiple research databases. Data were extracted using multiple variables that were formulated incongruent with the study aim and then further analyzed.Results A total of 79 studies were included in our analysis after applying the exclusion criteria and removing of repeated studies, 109 patients were identified where they were diagnosed with intracranial hemorrhage after spine surgery with a mean age of 54 years. The most common type of hemorrhage was cerebellar hemorrhage (56.0%) followed by SDH and intraparenchymal hemorrhage; 23.9 and 17.4%, respectively. The most common spine surgery was laminectomy (70.6%), followed by fixation and fusion (50.5%), excision of spinal lesions was done in 20.2% of the patient, and discectomy (14.7%).Conclusion The data in this study showed that out of 112 patients with ICH, cerebellar hemorrhage was the most common type. ICH post–spine surgery is a rare complication and the real etiologies behind this complication are still unknown, cerebrospinal fluid drain and durotomy were suggested.
Keywords: spinal surgery; intracranial hemorrhage; hematoma; hemorrhage